LEARNING STYLES IN RELATION TO ACADEMIC PERFORMANCE OF BTVTED STUDENTS - JOSE ARIEL IBARRIENTOS (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The study is a descriptive-correlational research which aims to determine the significant relationships between students’ learning styles and their academic performance. The study focuses on the learning styles of the first year BTVTRD students who are officially enrolled during the first semester of the school year 2019 – 2020. A survey is utilized in the collection of data while in its statistical analysis the Person Correlation Coefficient was employed. The results revealed that, on learning styles, diverse characteristics define the nature of learners in the BTVTED program. Their learning styles encompass physical, cognitive, affective, and physiological elements that influence learning. On academic performance, majority of the BTVTED students are classified above average. Applying the parametric test using Pearson Product – Moment Correlation, the study concludes that there is a significant relationship between students’ learning styles and their academic performance on the physical, cognitive, and physiological elements of learning. However, on its affective aspect, the contrary hypothesis is proved. Overall, the study finds the need for specific actions that will address the issue on pedagogical strategies employed in teaching the curriculum, approaches in the delivery of instructional content, monitoring, evaluation, and adjustments of key issues in the teaching and learning, institutional program to help students in difficult circumstances, and other studies that will help the college improve its quality education and services.